A human place in the sound of wildness. (16th March 2018) - Rothenberg, David
Abstract: What is the place for human sound in the beautiful world of nature? Will we ever be anything more than intruders in the midst of a pristine sonic wilderness? This essay considers what two of America's greatest field recordists, Lang Elliott and Gordon Hempton, think of such questions. If there is no place for our species in the result of field recording, that we cannot and should not record.